Особливості функціонування публіцистики в умовах 20−30-х рр. ХХ ст. на території Брестейщини - Борсук, Ніна; Borsuk, Nina (Волинський національний університет імені Лесі Українки, 2008)
Окреслена роль періодичних видань у вихованні політичної і національної свідомості мешканців Берестейщини. Показано, що об’єктивне освітлення подій на території БРСР викликало у західняків різне ставлення до Радянської влади і до боротьби проти колоніального пригнічення. Береться до уваги релігія, яка сприяла знищенню духовної культури народів . A rewiew of the role of periodicals in fostering the political and national consciousness of Brest region residents. An objective interpretation of events on the territory of the BSSR which aroused various feelings towards the Soviet Government and struggle against colonial oppression is given. Special attention is devoted to religion which favoured the preservation of the integrity of the nations’ cultural wealth.
The Peculiarities of the Functioning of Publicism in the Conditions of the 20s – 30s of the 20th Century on the Territory of Brest Region
Keywords: публіцистика; publicism; функціонування; functioning; полонізація; polonisation; свідомість; consciousness; індиферентність; indifference; західняки; Westerners; нотатки; sketches